PERSEPSI MAHASISWA AKUNTANSI UNESA TENTANG PENGARUH TRANSPARANSI DAN AKUNTABILITAS KEUANGAN PARTAI POLITIK TERHADAP KINERJA PARTAI DAN UPAYA PEMBERANTASAN KEJAHATAN KERAH PUTIH - Rohmah, Lailatur (Jurnal Akuntansi AKUNESA, 2014)
This research aims to determine the students perceptions of the impact accounting transparency and financial accountability for the performance of political parties and the party's efforts to combat white-collar crime. Object of this research is S1 Accounting program students study the class of 2010 and 2011 at the State University of Surabaya. The data used are primary data and secondary data. This research used descriptif research methods and judgment sampling. This research process questionnaire data which is the percentage of student response results. This research it can be seen that the transparency and accountability of political party finances are low. This affects the performance of the political parties and the decline in white-collar crime committed by members of a political party to be hard to be minimized.Keywords: Student Perceptions, Transparency and Accountability, the Performance of Political Parties, White Collar Crime.PENDAHULUAN